1977
DOI: 10.1139/m77-178
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between conidiation and alkaloid production in saprophytic strains of Claviceps purpurea

Abstract: A direct relationship between alkaloid synthesis and conidia formation was observed in a series of mutants of the saprophytic fungus Claviceps purpurea 129 which produces high quantities of clavine alkaloids (4500 microgram-ml-1). Sclerotia-like mutants forming mostly arthrospores and only a low number of conidiospores were exceptional in that they were characterized by an inverse relationship between alkaloid synthesis and conidial formation. Conidiospores of the parent strain 129 differed both in their size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1978
1978
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Several papers have shown that Aspergillus mutants deficient in sporulation are also unable to produce aflatoxin (see reference 12 and references therein). In 1977, it was shown that Claviceps purpurea mutants lacking the ability to form conidia on agar plates also produce less toxic alkaloids (93). In the same year, Sekiguchi and Gaucher (103) reported that P. urticae NRRL 2159A mutants blocked at an early stage of conidiation produced markedly less patulin under growth conditions which normally supported patulin biosynthesis.…”
Section: Mycotoxinsmentioning
confidence: 99%
“…Several papers have shown that Aspergillus mutants deficient in sporulation are also unable to produce aflatoxin (see reference 12 and references therein). In 1977, it was shown that Claviceps purpurea mutants lacking the ability to form conidia on agar plates also produce less toxic alkaloids (93). In the same year, Sekiguchi and Gaucher (103) reported that P. urticae NRRL 2159A mutants blocked at an early stage of conidiation produced markedly less patulin under growth conditions which normally supported patulin biosynthesis.…”
Section: Mycotoxinsmentioning
confidence: 99%
“…Obviously one is C. purpurea strain 129 described by PA2OUTOVA et al [19], which produces 4,5 g/l clavines predominantly agroclavine (76 %). One striking feature of this particular strain is the formation of micro-and macroconidia.…”
Section: Discussionmentioning
confidence: 99%
“…First, the stimulant may stimulate a physiological change in fungal cells with tentoxin as a product or a by-product of that physiological activity. For example, Pazoutova et al (21) reported a direct relationship between alkaloid synthesis and conidia formation in a series of mutants of the fungus Claviceps purpurea 129. This is similar to the result of another study in which we found that the addition of aged culture filtrate to cultures of A. alternata would also increase the sporulation of the fungus (unpublished data).…”
Section: Appl Environ Microbiolmentioning
confidence: 99%